The Role of Liaison Officers in Assisting MSMEs at a Business Expo Case Study of Es Jagung Gerai Mak Teh and Ice Bandung - Siti Aisah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Business expos provide strategic opportunities for Micro, Small, and Medium Enterprises (MSMEs) to introduce products, interact directly with consumers, and strengthen digital promotion. However, MSME participation requires effective coordination and continuous operational assistance. This study aims to analyze the role of Liaison Officers (LOs) in assisting MSMEs during the Polbeng Business Expo Chapter II, focusing on Es Jagung Gerai Mak Teh and Ice Bandung. A qualitative case study approach was employed. Data were collected through direct observation, interviews, documentation, activity records, promotional materials, transaction records, and simple financial reports. The data were analyzed through reduction, presentation, and conclusion drawing across the preparation, implementation, and evaluation stages. The findings show that LOs performed four integrated roles: liaison, coordinator, facilitator, and promotional assistant. During preparation, LOs identified tenant needs and developed business profiles, promotional videos, catalogs, and social media content. During implementation, they supported booth operations, customer service, direct promotion, communication with organizers, and QRIS-based transactions. During evaluation, they assisted in recording sales, preparing financial reports, and identifying operational challenges. All planned outputs were achieved, including two profile videos, two promotional videos, ten catalog designs, four social media platforms, two paid promotions, QRIS implementation for both MSMEs, and two financial reports. The study concludes that structured LO assistance strengthens MSME readiness, promotional reach, transaction convenience, and event coordination, although sustained post-expo support remains necessary to maintain long-term business impact.